Antimicrobial Use on 36 Beef Feedlots in Western Canada: 2008–2012 - Brault, Stephanie A.; Hannon, Sherry J.; Gow, Sheryl P.; Warr, Brian N.; Withell, Jessica; Song, Jiming; Williams, Christina M.; Otto, Simon J. G.; Booker, Calvin W.; Morley, Paul S. (Frontiers in Veterinary Science, 2019)
The accurate quantification of antimicrobial use (AMU) in production animals is critical for monitoring trends in exposure to antimicrobial drugs (AMD) over time and examining potential associations with antimicrobial resistance in bacteria. In this study, a census sample of cattle was used to quantify individually-dosed and in-feed AMU as both numbers of animal daily doses (nADD) and total grams of AMD (gAMD) used in cattle placed in 36 western Canadian feedlots between 1-November, 2008 and 31-October, 2012; representing about 21.5% of fed cattle in Canada during that time period. Of the approximately 2.6 million cattle placed during the 48-month period, 45% were calves, 63% were male, 62% arrived in the fall or winter, and 39% were assessed as high risk for developing bovine respiratory disease (BRD). The proportion of cattle categorized as high risk (HR) for developing BRD was consistent over the 4 years of placement cohorts. Use of medically important AMU and ionophore use was also summarized but was not combined with medically important AMU. A decrease in AMU was observed over the study period, both as nADD and total gAMD, which was primarily driven by a decline in the in-feed administration of tetracyclines. Most in-feed AMU was directed toward prevention and control of liver abscesses. The majority of individually dosed AMU was administered as metaphylaxis to address BRD risks, with category III AMDs (medium importance to human medicine as categorized by Health Canada Veterinary Drugs Directorate) used most frequently. Not surprisingly, risk level for developing BRD influenced parenteral AMD exposures, with 95% of cattle categorized as being HR for developing BRD receiving individually dosed AMDs compared to 59% of cattle categorized as being low risk (LR) for developing BRD. Cattle categorized as HR for developing BRD were more likely to receive macrolides for BRD metaphylaxis compared to cattle categorized as LR for developing BRD, and cattle categorized as LR for developing BRD were more likely to receive tetracycline for the same purpose. In summary, these data provide an unprecedented representation of AMU in fed cattle in western Canada and direction for future monitoring of AMU in fed cattle.